Alcohol, Tannins, and Mannoprotein and their Interactions Influence the Sensory Properties of Selected Commercial Merlot Wines: A Preliminary Study. Issue 8 (21st July 2016) - Diako, Charles; McMahon, Kenneth; Mattinson, Scott; Evans, Marc; Ross, Carolyn
Abstract: The objective of this study was to assess the influence of the interaction among alcohol, tannins, and mannoproteins on the aroma, flavor, taste, and mouthfeel characteristics of selected commercial Merlot wines. Merlot wines ( n = 61) were characterized for wine chemistry parameters, including pH, titratable acidity, alcohol, glucose, fructose, tannin profile, total proteins, and mannoprotein content. Agglomerative clustering of these physicochemical characteristics revealed 6 groups of wines. Two wines were selected from each group ( n = 12) and profiled by a trained sensory evaluation panel. One wine from each group was evaluated using the electronic tongue (e‐tongue). Sensory evaluation results showed complex effects among tannins, alcohol, and mannoproteins on the perception of most aromas, flavors, tastes, and mouthfeel attributes ( P < 0.05). The e‐tongue showed distinct differences among the taste attributes of the 6 groups of wines as indicated by a high discrimination index (DI = 95). Strong correlations ( r 2 > 0.930) were reported between the e‐tongue and sensory perception of sweet, sour, bitter, burning, astringent, and metallic. This study showed that interactions among wine matrix components influence the resulting sensory perceptions. The strong correlation between the e‐tongue and trained panel evaluations indicated the e‐tongue can complement sensory evaluations to improve wine quality assessment.